1979
DOI: 10.1111/j.1095-8649.1979.tb03643.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone binding to tissues of normal and stunted juvenile coho salmon, Oncorhynchus kisutch

Abstract: The premature transfer ofjuvenile Coho salmon into seawater results in high mortality and a reduction of growth (stunting) of a significant portion of the population while the remainder of the salmon continue to grow normally. Binding studies were conducted with 1251-labelled tilapia (Sarotherodon mossambicus) growth hormone (tGH) to determine if differences in specific binding of tGH existed in membrane preparations of tissues of stunted and normal coho salmon. Membrane preparations ofboth liver and gill of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…A similar correlation between reduced growth rate and blood GH elevation has been observed in the phenomenon of "stunting" in both coho and Atlantic salmon, Salmo s&r, smolts (Bolton et al, 1987;Bjornsson et al, 1988). However, the problem of suppressed growth in such stunts is thought to be related to target-tissue sensitivity rather than the rate of pituitary GH secretion (Fryer and Bern, 1979). Clearly much more information is now needed concerning the mechanisms of action of salmonid growth hormone in both normal and chronically stressed fish and the possible role of insulin-like growth factors or somatomedins in mediating these effects.…”
Section: Discussionmentioning
confidence: 77%
“…A similar correlation between reduced growth rate and blood GH elevation has been observed in the phenomenon of "stunting" in both coho and Atlantic salmon, Salmo s&r, smolts (Bolton et al, 1987;Bjornsson et al, 1988). However, the problem of suppressed growth in such stunts is thought to be related to target-tissue sensitivity rather than the rate of pituitary GH secretion (Fryer and Bern, 1979). Clearly much more information is now needed concerning the mechanisms of action of salmonid growth hormone in both normal and chronically stressed fish and the possible role of insulin-like growth factors or somatomedins in mediating these effects.…”
Section: Discussionmentioning
confidence: 77%
“…data), this variability can be explained in part by the different sexual stages and degrees of nutrition of the animal used in this study. Fryer and Bern (1979) and more recently Gray et al (1989) demonstrated that specific binding of GH is lower in stunted than in normal coho salmon. In mammals, variations of GH binding were also observed during pregnancy (Posner, 1976;Gerasimo et al, 1979) and starvation (see Postel-Vinay et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Using this last hormone, specific binding was also found in the liver of mudsucker, rainbow trout (Oncorhynchus mykiss), and chinook salmon (0. tshawytschu) (Fryer, 1979b), and one study indicated that stunted coho salmon (0. kisutch) have a decreased ability to bind GH by liver (Fryer and Bern, 1979). More recently, using chinook salmon GH, we demonstrated the presence of saturable binding in rainbow trout liver (Le Bail et al, 1989;Niu et al, submitted for publication).…”
mentioning
confidence: 87%
“…Their number are modulated by stunting (Fryer and Bern 1979;Gray et al 1990), salinity (Sakamoto and Hirano 1991), GH plasma levels, temperature or starvation (P6rez-Sanchez et al 1991;Yao and Le Bail, unpublished data). However, GH receptors may not the only element involved in the receptivity of target tissues to GH.…”
Section: Introductionmentioning
confidence: 95%